Mídia-educação e relações públicas: uma prática transformadora - Boaventura, Marina da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The present project has as principal theme the education for the media. Considering the onipresent of the media in our day by day, it is believed to be of crucial matter that the individuals are capable to do a creative and critical use of the media content. For this, the text addresses some concepts and the historical traject of the media literacy, just like your perspectives of study in the areas of Comunication and Education. Observed the caracteristics and the metodology of media literacy, it has as this project principal intent, the inclusion of the theme in the academical extent for the students of Public Relations at Universidade Estadual Paulista (UNESP). The study improves with the aplication of questionaries and the observation of discussions performed at classes with the students, demonstrating, therefore, the important in develop actions of educative character in the atuation of the Public Relation career. Alliyng actions of media literacy and Public Relations in the organizational environment, concludes that its possible to work with the formation of the internal public, expanding their empowerment as citizen and searching more participation in discussion as the gender issue in the organizations

A presente pesquisa tem como tema principal a educação para as mídias. Considerando a onipresença das mídias em nosso cotidiano, acredita-se ser de suma importância que os indivíduos sejam capazes de fazer um uso crítico e criativo do conteúdo midiático. Para isso, o texto aborda alguns conceitos e a trajetória histórica da mídia-educação, bem como suas perspectivas de estudo nas áreas da Comunicação e Educação. Observadas as características e a metodologia de mídia-educação, têm-se como objetivo principal desta pesquisa a inclusão do tema no âmbito acadêmico para os alunos do curso de Relações Públicas da Universidade Estadual Paulista (UNESP). O estudo se aprofunda com a aplicação de questionário e da observação de debate realizados em aula com os alunos, demostrando, assim, a importância em desenvolver ações de caráter educativo na atuação do profissional de Relações Públicas. Ao aliar ações de mídia-educação e Relações Públicas no âmbito organizacional, conclui-se que é possível trabalhar com a formação do público interno, ampliando seu empoderamento como cidadão e buscando maior participação em debates como a questão do gênero nas organizações
Keywords: Comunicação; Relações publicas; Mídia social; Cidadania; Communication